Case report: Cavernous hemangioma in the right frontoparietal junction - Cao, Xuemin; chen, xiaoshuai; wang, yi; feng, shangang; wang, zengwu (Frontiers in Surgery, 2022)
Background：Primary intraosseous cavernous hemangioma is a benign, slow-growing tumor that is clinically rare. Most patients present clinically with a progressively enlarging mass in the head. Case presentation：We present a case of a 30-year-old female patient with a cavernous hemangioma of the frontoparietal junction who was admitted to the hospital with a "progressive enlargement of the right frontal mass for 3 years" and underwent surgical excision of the lesion and phase I cranial reconstruction. The postoperative outcome was good, with no recurrence at 1 year follow-up. Conclusions：Primary intraosseous cavernous hemangioma is a relatively rare clinical tumor, the pathogenesis of which is still unclear, and most of them have no specific clinical manifestations. Characteristic imaging findings are highly suspicious of this disease, but the definitive diagnosis still depends on histopathological examination. Currently, total surgical resection of the tumor is a relatively effective and preferred treatment.